Vibration Analysis and Control New Trends and Developments - Beltran-Carbajal, Francisco (IntechOpen, 2011)
This book focuses on the important and diverse field of vibration analysis and control. It is written by experts from the international scientific community and covers a wide range of research topics related to design methodologies of passive, semi-active and active vibration control schemes, vehicle suspension systems, vibration control devices, fault detection, finite element analysis and other recent applications and studies of this fascinating field of vibration analysis and control. The book is addressed to researchers and practitioners of this field, as well as undergraduate and postgraduate students and other experts and newcomers seeking more information about the state of the art, challenging open problems, innovative solution proposals and new trends and developments in this area.